Text, cases, and materials on public law and human rights - Fenwick, Helen; Phillipson, Gavin (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2011)
This book draws together a comprehensive range of sources with the aim of allowing the reader to study the subject in depth, examining constitutional theory, the operation of the constitution and the legal protection for civil liberties